Overview of Robotic Reducer Testing Technology. Issue 1 (August 2021) - Lin, Yuanchang; Sun, Wencheng; He, Guotian; Zhang, Zhenjun
Abstract: As a high-performance precision reduction transmission equipment with large transmission ratio, high transmission efficiency, high transmission accuracy, stable transmission and low noise, reducer has been widely used in many fields such as industrial robots. The definition of the reducer is studied, the development history of the reducer is briefly introduced, and the classification and characteristics of the reducer are summarized, including traditional reducer, RV reducer, harmonic planetary reducer and cycloid reducer, A new generation of reducer and influencing factors such as transmission accuracy, transmission efficiency, backlash, torsional stiffness, noise, and assembly. The problem of precision reducer is analyzed, and finally the application and development trend of reducer are studied.